MONISEDA Project: Improving Analgosedation Monitoring in Spanish Pediatric Intensive Care Units - Mencía, Santiago; Cieza, Raquel; del Castillo, Jimena; López-Herce, Jesús; , Sedation Group of Spanish Pediatric Critical Care Society (SECIP); Tapia, Rocío; Borrego, Raúl; Domínguez, Mercedes; Calvo, Cristina; Fernández, Francisco; Nieto, Manuel; Estalella, Ana; et al. (Frontiers in Pediatrics, 2021)
Background: Analgosedation (AS) assessment using clinical scales is crucial to follow the international recommendations about analgosedation. The Analgosedation workgroup of the Spanish Society of Pediatric Intensive Care (SECIP) carried out two surveys in 2008 and 2015, which verified the gap in analgosedation assessment in Spanish PICUs. The objective of the study was to analyze how analgosedation assessment by clinical scales changed after a multicenter intervention program. Methods: multicenter pre-post study comparing the use of sedation, analgesia, withdrawal and delirium scales before and after the MONISEDA project. Results were also compared with a control group formed by non-participating units. A survey about analgosedation management and monitoring was filled out before (year 2015) and after (year 2020) the implementation of the Moniseda project in 2016. Results were compared between those periods of time, but also between participant and non-participants PICUs in the Moniseda project (M-group and non-M group, respectively). Data related to analgosedation of all patients admitted to a Moniseda-participant PICU were also collected for 2 months. Results: 15 Spanish PICUs were enrolled in the Moniseda project and other 15 non-participant PICUs formed the control group. In the M-group, the number of PICUs with a written analgosedation protocol increased from 53 to 100% (p=0.003) and withdrawal protocol from 53 to 100% (p=0.003), whereas in non-M group the written AS protocol increased from 80 to 87% and withdrawal protocol stayed on 80%. The number of PICUs with an analgosedation team increased from 7 to 47% in the M-group (p=0.01) and from 13 to 33% in the non-M group (p=0.25). In the M-group, routine use of analgosedation clinical scales increased from 7 to 100% (p<0,001), withdrawal scales from 7 to 86% (p=0.001) and delirium scales from 7 to 33% (p=0.125). In the non-M group the number of PICUs using AS scales increased from 13 to 100% (p<0.001), withdrawal scales from 7 to 27% (p=0.125) and delirium scales from 0 to 7% (p=1). Conclusions: Development of a specific training program improves monitoring and management of analgosedation in PICUs.